CaFe-Based Layered Double Oxides With Superior Iron Alloy Corrosion Inhibition Behaviors in Aggressive Seawater Environment - Park, Ji Young; Yoo, Su Been; Cho, Hong-Baek; Lee, Han-Seung; Choa, Yong-Ho (Frontiers in Chemistry, 2022)
Reinforced concrete is among the most multifaceted materials used in the construction field. Maintaining the resistance of reinforced concrete to weathering, abrasion, and chemical attack, particularly in aggressive natural conditions such as seawater environments, is challenging. The main factor in the degradation of reinforced-concrete durability is chloride penetration, which accelerates iron alloy corrosion and facilitates structural degradation. In this study, calcium-iron-based layered double hydroxides (CaFe-LDHs) were fabricated at room temperature, followed by structural modulation, and their effectiveness in mitigating iron alloy corrosion due to chloride ions (in 3.5 wt% of NaCl) was investigated. The synthesized CaFe-LDHs with phase transfer notably improved the Cl- removal capacity (Qmax) to 881.83 mg/g, which is more than three times that reported based on previous studies. The novelty of this research lies in the sophisticated structural and phase transformations of the as-synthesized CaFe-LDHs, determination of crucial factors for chloride ion removal, and suggestion of calcium-iron-based layered double oxide (CaFe-LDO)-based chloride ion removal mechanisms considering chemical and ion-exchange reactions. Moreover, when the phase-transformed LDHs, C-700 LDOs, were applied to inhibit iron alloy corrosion, a noticeable inhibition efficiency of 98.87% was obtained, which was an 11-fold improvement compared to the case of iron alloys without LDOs. We believe this work can provide new insights into the design of CaFe-LDOs for the enhancement of the lifespan of reinforced concrete structures.